2003
DOI: 10.1097/00006454-200301000-00015
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to prescribed antiretroviral therapy in human immunodeficiency virus-infected children in the PENTA 5 trial

Abstract: Good adherence with taking prescribed medication was associated with virologic response. Social factors were important in explaining nonadherence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
110
2
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(119 citation statements)
references
References 13 publications
6
110
2
1
Order By: Relevance
“…1,2,6,7,10,[12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] The interview guidelines (Table 1) contained 4 broad topics: self-report of adherence, factors that influence adherence, assistance in the child's medication intake, and personal perspectives.…”
Section: Methodsmentioning
confidence: 99%
“…1,2,6,7,10,[12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] The interview guidelines (Table 1) contained 4 broad topics: self-report of adherence, factors that influence adherence, assistance in the child's medication intake, and personal perspectives.…”
Section: Methodsmentioning
confidence: 99%
“…43,44 Studies have demonstrated better adherence with a twice-per-day (vs 3-times-per-day) nelfinavir regimen, shorter length of time since treatment initiation, and nelfinavir rather than indinavir but not with pill burden or drug toxicity. 18,29,35,36 Pontali 43 cited such factors as the availability and cost of the medications, accessibility of treatment, and health care providers' experience and relationship to the patient as health care system variables that are possibly associated with adherence.…”
Section: Factors Related To Adherencementioning
confidence: 99%
“…19 Impediments to adherence for young people have been broadly categorised into two main groups: problems with medication, such as taste and palatability issues, and adherence difficulties related to social situations. 20 Although there have been considerable attempts to improve drug formulations, thus partly addressing the first impediment, the social dimensions are more complex; interference with daily life recurs as a common theme in assessments of poor adherence in young people.…”
Section: Discussionmentioning
confidence: 99%
“…Jacobsen et al, 24 in a four-arm study of planned treatment interruption ± HIV immunisation, reported viral rebound to > 50 copies/ml following treatment interruption at a median [interquartile range (IQR)] of 15 days for those with a prior planned treatment interruption and 21 (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) days for those without a prior planned treatment interruption. Harrigan et al, 35 while assuming a constant rate of viral increase that starts as soon as the patient stops therapy, suggest that many patients stopping therapy (previously suppressed) will have an increase in plasma viral HIV ribonucleic acid (RNA) of about 0.2 log/day and will reach detectable levels (> 50 copies/ml) only within 1-2 weeks of stopping therapy.…”
Section: Antiretroviral Agents Viral Load Rebound and Resistancementioning
confidence: 99%